2019
DOI: 10.1016/j.cmi.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of missed bloodstream infections without the third blood culture set: a retrospective observational single-centre study

Abstract: Our data suggest that performing a third BCS is useful, as not doing this could result in an unacceptable number of BSIs going undetected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In this study, three blood cultures of 20 ml detected 98.2% of BSI and only with four blood cultures, >99% of BSI episodes were detected. Another recent study confirmed the need for at least three blood cultures (or 60 ml) to be sampled, as they found that 7.5% of BSI episodes would have been missed without a third blood culture (157).…”
Section: Methods and Techniques For Processing Manual Blood Culturesmentioning
confidence: 87%
“…In this study, three blood cultures of 20 ml detected 98.2% of BSI and only with four blood cultures, >99% of BSI episodes were detected. Another recent study confirmed the need for at least three blood cultures (or 60 ml) to be sampled, as they found that 7.5% of BSI episodes would have been missed without a third blood culture (157).…”
Section: Methods and Techniques For Processing Manual Blood Culturesmentioning
confidence: 87%
“…This critical factor drove one fundamental change in automated blood culture systems: the need for capacity to accommodate three or more sets of bottles from a blood cultures series and enable the management of a larger number of bottles to conform to guidelines [7,34,35]. At the same time, in order to accommodate more bottles per instrument, the time required to test each bottle needed to drop substantially.…”
Section: Number Of Blood Culturesmentioning
confidence: 99%
“…-Recommendations for complete BC sampling suggest at least two sets, corresponding to 30-40 mL in total [24], subdivided into four BC bottles, two for aerobic and two for anaerobic organisms; the aerobic bottle should be filled first. BC should take priority in the case of several specimens from the same venipuncture [26,28,[34][35][36][37][38][39][40]. -Recently, a retrospective study of 4000 BSI episodes demonstrated that without a third BC set, 7.9% of BSIs would have been missed, although in 33.9% of the missed episodes, the same organism recovered in the third BC was isolated in other clinical specimens (i.e.…”
Section: Blood Volumementioning
confidence: 99%
“…-Recently, a retrospective study of 4000 BSI episodes demonstrated that without a third BC set, 7.9% of BSIs would have been missed, although in 33.9% of the missed episodes, the same organism recovered in the third BC was isolated in other clinical specimens (i.e. urine) for an actual rate of approximately 5% [39]. -The practice of a "solitary BC" (only two bottles or one set), although still common, is not acceptable and should be actively discouraged [8,28,35].…”
Section: Blood Volumementioning
confidence: 99%